Contemporary teaching of posterior composites at dental schools in Austria, Germany, and Switzerland. (May 2020) - Kanzow, Philipp; Büttcher, Amelie F.; Wilson, Nairn H.F.; Lynch, Christopher D.; Blum, Igor R.
Abstract: Objective: To investigate current teaching and operative techniques for posterior composite resin restorations in dental schools in Austria, Germany, and Switzerland. Methods: Data on teaching, including operative techniques applied in the placement of posterior composites, were collected by means of a 25-item validated questionnaire sent to the Heads of Department of Operative/Restorative Dentistry at all 38 dental schools in Austria, Germany, and Switzerland. Responses were compiled in Excel and analysed. Results: Thirty-three schools responded to the survey, resulting in a response rate of 87 %. All dental schools indicated teaching of 2- and 3-surface posterior composite restorations. About one third only of the preclinical teaching is assigned to teaching posterior composite restorations, while the vast majority of posterior restorations placed by students in their clinical instruction are composite (89.6 ± 9.3 %). Most dental schools teach few contraindications to posterior composites, except for adverse reactions such as allergies. All dental schools consider moisture control to be important, while approaches to the management of exposed dentine differ. Conclusions: The teaching of the placement of posterior composite restorations is common to all the dental schools in Austria, Germany, and Switzerland which participated in the present study. Most aspects of the teaching were found to be consistent amongst the schools. However, marked variations were observed in respect of operative techniques for the placement of posterior composites. Clinical significance: Graduates from dental schools in Austria, Germany, and Switzerland may be found to have received theoretical, preclinical, and clinical instruction in posterior composites, but do show some variation in approach to the management of exposed dentine.